A wideband planar filtering dipole antenna for 5G communication applications. Issue 12 (25th July 2019) - Xi, Lei
Abstract: A wideband planar filtering dipole antenna for 5G communication applications is proposed in this article. The proposed dipole antenna is composed of two rectangle radiation patches, fed by the inverted L‐shaped feedline. Because of the gradient feedline, a wideband dipole antenna is obtained. Two complementary stepped impedance resonators (CSIRs) branches and two complementary split‐ring resonators (CSRRs) are etched on the radiating rectangular patches so that the antenna produces under and upper resonant zeros out of the operating band. The reflection coefficient of the mentioned antenna is <‐10 dB in 3.08 to 5.15 GHz (50.3%). In the working frequency band, the radiation pattern of the antenna is very stable. In the desired frequency bands, the antenna gain is >2 dBi. Specially, there are above 23 dB radiation suppression for gain in the out of band. Finally, the filtering dipole antenna is processed and fabricated, and the measured results are consistent with the simulation results.